Consensus guidelines for the use of empiric and diagnostic‐driven antifungal treatment strategies in haematological malignancy, 2014. Issue 12 (December 2014) - Morrissey, C. O.; Gilroy, N. M.; Macesic, N.; Walker, P.; Ananda‐Rajah, M.; May, M.; Heath, C. H.; Grigg, A.; Bardy, P. G.; Kwan, J.; Kirsa, S. W.; Slavin, M.; et al.
Abstract Invasive fungal disease (IFD) causes significant morbidity and mortality in patients undergoing allogeneic haemopoietic stem cell transplantation or chemotherapy for haematological malignancy. Much of these adverse outcomes are due to the limited ability of traditional diagnostic tests (i.e. culture and histology) to make an early and accurate diagnosis. As persistent or recurrent fevers of unknown origin (PFUO) in neutropenic patients despite broad‐spectrum antibiotics have been associated with the development of IFD, most centres have traditionally administered empiric antifungal therapy (EAFT) to patients with PFUO. However, use of an EAFT strategy has not been shown to have an overall survival benefit and is associated with excessive antifungal therapy use. As a result, the focus has shifted to developing more sensitive and specific diagnostic tests for early and more targeted antifungal treatment. These tests, including the galactomannan enzyme‐linked immunosorbent assay and Aspergillus polymerase chain reaction (PCR), have enabled the development of diagnostic‐driven antifungal treatment (DDAT) strategies, which have been shown to be safe and feasible, reducing antifungal usage. In addition, the development of effective antifungal prophylactic strategies has changed the landscape in terms of the incidence and types of IFD that clinicians have encountered. In this review, we examine the current role of EAFT and provide up‐to‐date data on the newer diagnostic tests and algorithms available for use in EAFT and DDAT strategies, within the context of patient risk and type of antifungal prophylaxis used.